Thistle and Bamboo : the Life and Times of Sir James Stewart Lockhart. - Airlie, Shiona, 1953- (Echoes (Hong Kong, China), 2010)
Colonial civil servant, Confucian scholar, and collector of Chinese art, Sir James Stewart Lockhart spent more than forty years in Hong Kong and Weihaiwei -- the former British leased territory in northern China. His career reflects tension and upheaval in the emerging colony of Hong Kong and in a China rapidly giving way to civil war. In her vivid biography of Stewart Lockhart, Shiona Airlie presents a portrait of an imperial official who fought against racism, strove to preserve the Chinese way of life, and was treated by Chinese mandarins as one of their own. Sir James Stewart Lockhart (1858.